PENGARUH PENDIDIKAN DAN PELATIHAN, PENGEMBANGAN KARIR DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT. Bina Busana Internusa Semarang) - Sinurat, Bistok Surya Rahara; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2017)
Employees are the human resources that are needed in achieving companies goals. Therefore, companies need to pay attention to the good performance of employees. Problems that occur in this study is the declining performance of employees at PT. Bina Busana Internusa Semarang. This study aims to investigate the influence of education and training, career development and job satisfaction on employees performance at PT. Bina Busana Internusa Semarang.This study uses data collection using a questionnaire with random sampling method. The sample used in this study were permanent employees of PT. Bina Busana Internusa Semarang with the number of respondents was 83. This study uses data analysis methods include reliability test, validity test, classic assumption test, multiple linear regression analysis, F test and t test and also the coefficient of determination test.The results showed that the variables of education and training, career development and job satisfaction have a positive influence on employee performance. The independent variables impact of 75% on the performance of employees at PT. Bina Busana Internusa Semarang.